Safeguarding Stability and Enhancing Profitability: The Case of Islamic Banking in Indonesia - Mubarok, Faizul; Wibowo, Martino; Latif, Sahraman D Hadji (Universitas Muhammadiyah Yogyakarta, 2024)
This study examines the impact of crises, non-performing financing variables, exchange rates, inflation, and interest rates on Islamic banks' short-term and long-term profitability in Indonesia. Profitability (ROA) fluctuations are also assessed in consideration of exogenous shocks. This analysis uses the Vector Error Correction Model (VECM) to examine monthly data from 2007 to 2023. The results suggest that non-performing financing (NPF), exchange rates (BIRT), and inflation (IFLS) have a substantial impact on the long term. While the crisis variable exhibits a relatively less substantial influence, interest rates reveal distinct short-term and long-term impacts. The Impulse Response Function data indicate that NPF, KURS, and IFLS have a negligible effect on ROA. NPF primarily influences ROA variation, as determined by the Forecast Error Variance Decomposition; KURS follows suit. Islamic Banks' management must diligently oversee non-performing loans, exchange rates, and inflation and astutely devise interest rate strategies. The factors impacting the profitability of Islamic banks in Indonesia are thoroughly examined in this study.